If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8f + -7f + 7 = 19 Reorder the terms: 7 + 8f + -7f = 19 Combine like terms: 8f + -7f = 1f 7 + 1f = 19 Solving 7 + 1f = 19 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1f = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 1f = 19 + -7 1f = 19 + -7 Combine like terms: 19 + -7 = 12 1f = 12 Divide each side by '1'. f = 12 Simplifying f = 12
| 2y=1.6 | | 4(v-2)-8v=32 | | 175x=300x-4500 | | 4(n+4)=-12 | | 7=6+2x-5 | | 11x-7=4x+10 | | 175/x-15=300/x | | X=-4y+6z-5x-6x+y | | 12x^2+2x+1=0 | | 2q+2(-5+5g)=1-g | | (X-32)(x-17)=0 | | solvex-2(x+3)=-2(x-1)-4 | | m-9.5+7.8= | | (1+w)(3w-7)=0 | | 4x-2=8x+4 | | 2x+9y=38 | | -22-w=8(6-8w)-7 | | y=6x^2-8 | | 14=5-3x | | -3+2m=-15 | | 81607=n+73142 | | 2k+4=5k-4 | | 81,607=n+73,142 | | 28-d=14 | | -(7x-4)+5x-8=-4 | | .8x-.1=.3 | | 145=-98 | | 16t^2-27t+10=0 | | 8y+3=35 | | 11x+11=9x+23 | | 8-12s=32 | | 3s-1=4s+5 |